Prevalence of lifestyle diseases in Goa: a comparison between NFHS-5 and NFHS-6 - Myla Isha Pereira; Sandesh Chodankar; Chitralekha Nayak; Maheen Noushad; Aishwarya Loliyekar; Krishna Prakash P. (International Journal Of Community Medicine And Public Health, 2026)
Non-communicable diseases (NCDs) account for 74% of all global deaths and represent the foremost public health challenge of the twenty-first century. India is home to over 101 million adults with diabetes, the second-highest national burden in the world, and an estimated 315 million with hypertension. Goa, with its high urbanisation, above-average per capita income, rapidly ageing population, and distinct dietary practices, is expected to be at an advanced stage of India’s epidemiological transition. The sixth round of the National Family Health Survey (NFHS-6, 2023-24), released by the Ministry of Health and Family Welfare in May 2026, provides, for the first time, the opportunity to compare key lifestyle disease indicators in Goa across two consecutive NFHS rounds. This study undertakes a comparative secondary analysis of published state and national fact sheet data for three core indicators: overweight/obesity, hyperglycaemia, and hypertension, disaggregated by sex and residential setting. The findings reveal a sharp and accelerating rise in obesity, from 36.1% to 45.1% among women (+9.0 percentage points) and from 32.6% to 43.6% among men (+11.0 pp), both exceeding the national trajectory. Hyperglycaemia similarly rose from 20.8% to 27.5% in women (+6.7 pp) and from 24.1% to 32.1% in men (+8.0 pp), with Goa’s rates substantially above national averages. Hypertension remained stable overall, but with a notable compositional shift towards better pharmacological control. These findings place Goa’s NCD burden among the highest in India and call for urgent, evidence-based community medicine responses, including population-level obesity prevention, expanded metabolic screening, and culturally adapted dietary intervention.